Lime mortars for masonry repair: Analytical science and laboratory testing versus practical experience - PAVIA, SARA (My University, 2006)
This paper addresses the decay and performance of lime mortars used for repairs to masonry fabrics. It sets out how analytical science, laboratory testing and practical experience contribute to the diagnosis of mortar failure and decay, and how these also contribute to the formulation of conservation and repair solutions. It compares data obtained from the petrographic analysis of historic and traditional lime mortars with laboratory testing of new repair mixes and practical experience. This paper demonstrates that the best conservation theories can be formulated and the best conservation practice achieved when both analytical science and laboratory testing are coupled to the practical experience arising from the exercise of craft and material technology.
PUBLISHED
Keywords: lime mortar decay and conservation; petrographic analysis